The 1320 Ma intracontinental Wongawobbin Basin, Pilbara, Western Australia: A far-field response to Albany–Fraser–Musgrave tectonics - Sheppard, S.; Krapež, B.; Zi, Jianwei; Rasmussen, Birger; Fletcher, I. (Elsevier BV, 2016)
The Eel Creek Formation, which crops out along the northeastern edge of the Archean Pilbara Craton in Western Australia, is a formerly undated, siliciclastic succession with a preserved thickness of at least 500 m. Only a small portion of the basin is exposed at surface; the bulk of it is buried beneath Neoproterozoic and Phanerozoic basins. Two tuff samples from near the base of the succession have SHRIMP U–Pb zircon ages of 1318 ± 7 Ma and 1310 ± 8 Ma, which are interpreted to be igneous crystallization ages. These depositional ages are indistinguishable from a SHRIMP U–Pb zircon date of 1317 ± 11 Ma previously obtained for a tuff about 80 km to the south-southeast at Ripon Hills. The three dates indicate that sedimentation and minor felsic volcanism at c. 1320 Ma extended over a minimum distance of 110 km along the eastern margin of the Pilbara Craton. The succession at Ripon Hills has been interpreted as an outlier of the Manganese Group, but current evidence is consistent with partial correlation between the c. 1070 Ma Collier Group and the Manganese Group. Therefore, correlation of the succession at Ripon Hills with the c. 1320 Ma Eel Creek Formation is more likely. We propose that both sequences are components of the newly named Wongawobbin Basin, an intracontinental basin that formed in response to far-field stress associated with the Albany–Fraser Orogen of southeast Western Australia and the Musgrave Orogen of central Australia. The Eel Creek Formation was sourced mainly from the Pilbara Craton, but with a minor contribution from the Archean Gregory Range Inlier and the Paleoproterozoic Rudall Province to the southeast.